Does childhood and adolescence provide a unique opportunity for exercise to strengthen the skeleton? - Khan, K.; McKay, H. A.; Haapasalo, H.; Bennell, K. L.; Forwood, M. R.; Kannus, P.; Wark, J. D. (Journal of Science and Medicine in Sport, 2000)
Osteoporosis is a major, and increasing, public health problem. In this review we examine the evidence that childhood physical activity is an important determinant of bone mineral in adult years, and as such, may help to prevent osteoporosis. Animal studies provide incontrovertible evidence that growing bone has a greater capacity to add new bone to the skeleton than does adult bone. Observational studies in children undertaking routine physical activity and cross-sectional athlete studies in young sportspeople both reveal that activity is positively associated with bone mineral density (BMD). Longitudinal studies in pre- and peripubertal gymnasts reveal BMD gains far in excess of those that can be achieved in adulthood. However, such studies permit only limited conclusions as they contain the potential for selection bias and can be confounded by other determinants of bone mineral (e.g. dietary and lifestyle factors). Thus, research comparing inter-individual playing-to-nonplaying arm differences in bone mineral (e.g., in racquet sports) have proven to be extremely useful. These studies suggest that the BMD differences are clearly greater when bone is subjected to mechanical loading prior to the end of puberty and longitudinal growth of the body (in women, before menarche) rather than after it. Tanner stage II and III appears to be the maturational stage when the association between exercise and BMD becomes manifest in most adolescents. Do conclusions drawn from athlete studies apply to the general population? Randomised intervention studies of physical activity and bone mineral accrual in normal children confirm that childhood activity is strongly associated with bone mineral accrual. Furthermore, some retired athlete studies and a detraining study suggest that adolescent bone gain may, at least partly, persist despite reduced adult physical activity. Mechanisms that may underlie the association between childhood physical activity and bone mineral accrual are outlined. Thus, it appears that physical activity during the most active period of maturity (with respect to longitudinal growth of the body) plays a vital role in optimising peak bone mass and that benefits may extend into adulthood.